Morphological response to climate-induced flood-event variability in a subarctic river - Blåfield, Linnea; Gonzales-Inca, Carlos; Alho, Petteri; Kasvi, Elina (Copernicus GmbH, 2026)
This study examined the effects of climate-induced flood-event variability and peak sequencing on morphological response and sediment transport hysteresis patterns in a subarctic river. We classified 32 years of discharge hydrographs from a subarctic river according to their spring flood hydrograph shapes and peak sequences. These classified flood-event types and their frequencies were statistically analysed against seasonal and annual climatic conditions from the corresponding time periods. Morphodynamic modelling was employed to examine the effects of flood-event hydrograph shape and sequencing on morphological response and sediment transport hysteresis patterns during floods. The findings highlight the critical role that hydrograph shape and sequencing play in influencing river morphology and sediment transport dynamics, as each flood-event type produced distinct sediment transport hysteresis patterns and morphological outcomes. Variance and trend analyses revealed that prevailing climatic conditions significantly influence the hydrograph shapes of spring flood events. Annual mean temperature, total precipitation, and snow accumulation, together with cold season mean temperature, spring rainfall, and May cumulative temperature, had the greatest effect on the type of spring flood event observed. Significant increasing trends were identified in annual and spring mean temperatures, spring rainfall, and the frequency of rain-on-snow events. This suggests that ongoing climatic shifts are actively modifying the nature of spring flood events, favouring more complex and variable hydrograph forms. Consequently, future sediment transport and morphological evolution in subarctic rivers are likely to become increasingly event-driven, less predictable, and more sensitive to interannual climatic variability. These changes emphasize the need for adaptive management strategies that can accommodate the emerging hydrological and geomorphological dynamics under a changing climate.